Drug utilization study of anti-hypertensive drugs at a tertiary care hospital - Ahluwalia, Pritpal Singh; Baig, Mirza Shiraz; Bhattacharya, Meenakshi (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The increasing prevalence of hypertension influence the prescribing patterns of antihypertensive drug. Prescribing against evidence-based guidelines in hypertension treatment leads to the increase cost of medications and problems in providing affordable prescriptions to population. The aim of present study was to analyse anti-hypertensive prescribing pattern in Government Medical College and Hospital, Aurangabad, Maharashtra, India. Methods: Study was prospective, observational, open label and descriptive clinical study. It included 336 patients admitted in MICU during January 2018 to June 2019 fulfilling inclusion criteria. Results: 54.46% patients were between 51-70 years of age, followed by 33.63% in 31 to 50 age group. Of total enrolled hypertensive patients 69% patients had various comorbidities. Drug prescribed was 28.27% ARBs, 26.84% CCBs, 17.62% beta blockers, 6.14% high ceiling diuretics, 4.50% ACE inhibitors, 2.45% thiazide diuretics and 2.04% received alpha blocker. As monotherapy, 31.82% patients received telmisartan as most commonly prescribed drug followed by 27.31% patients received Amlodipine followed by other drugs. In combination therapy telmisartan and hydrochlorothiazide was prescribed most commonly followed by beta blocker and CCB and ARB and CCB. 33.60% of drugs were prescribed in generic names while 66.39% of drugs prescribed in brand names. Average number of drugs prescribed per prescription was 1.45 of which 33.60% of drugs were prescribed by generic names. Conclusions: With average number of drugs per prescription in hypertension 1.45, the study showed that poly pharmacy is unavoidable in hypertension due to associated comorbid conditions.